Features of American slang and ways of its translation - Alimova Gulnazkhon Yuldashaliyevna; Tokhtakulova Oygul Khasan kizi (Periodica Journal, 2023)
This article discusses the features of American slang and the ways of translation. Specific characteristics of slangs were determined and examples were given. What problems arose in the translation of slangs and their elimination were reflected. The classification of the concept of slangs and its role in the language were explained
Keywords: American slang; slangs; functions of slangs